PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK MATA PELAJARAN INFORMATIKA KELAS VIII UPT SMP NEGERI 2 BARANTI KABUPATEN SIDENRENG RAPPANG - Muhammad Fadli A. Wahid; Nurmayanti; Hasanuddin B. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This development research aims to develop Flipbook learning media. This research is a research and development (R&D) study using the ADDIE development model, which consists of five stages, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. Data collection techniques used observation, interviews, documentation, questionnaires, and tests. The results of the study show that (1) the average validation score was 84% (highly valid), (2) the average questionnaire score was 89% (highly practical), and (3) the N-gain score was 84% (effective). Based on this data, it can be concluded that the Flipbook learning media can be used in the Informatics learning process in Grade VIII at UPT SMP Negeri 2 Baranti Sidenreng Rappang Regency.